Modele regulacji ludowej inicjatywy ustawodawczej: [Models of legal regulations of popular legislative initiative] (Studia Prawnicze / The Legal Studies, 2007)
Ludowa inicjatywa ustawodawcza jest mało znaną i rzadko spotykaną instytucją w prawodawstwach państw europejskich. Inicjatywa ta jest prawem pewnej liczby obywateli do złożenia wniosku w określonej sprawie w celu uchwalenia ustawy. Tylko nieliczne państwa posiadają w swym ustawodawstwie przepisy, które by regulowały ten rodzaj inicjatywy ludowej, przy czym sposób uregulowania jest zróżnicowany, od bardzo sformalizowanego do całkiem schematycznego i pobieżnego. Wszędzie uważana jest za ważny element ustroju i istotne uzupełnienie demokracji parlamentarnej.W niniejszym opracowaniu postaram się przybliżyć dwa odmienne sposoby uregulowań tej inicjatywy na przykładzie Austrii i Polski.  Popular legislative initiative is not a well-known and common institution in legał systems of European countries. The initiative is the right of a specified number of citizens to lodge a petition for enacting a certain law. This type of popular initiative is regulated only in a few countries where regulations vary from formalized to schematic and superficial. However, there is no doubt that popular legislative initiative is considered as a significant supplement of parliamentary democracy.There are two main types of legał regulations conceming popular legislative initiative.The first one can be found in the Polish legał system where the whole burden of organizing popular initiative (conceming e.g.: establishing the initiative committee, collecting reąuired number of signatures, financing all the activities associated with the initiative) is put on the initiative’s organizers, whereas public authorities do not assist.The second type can be found in Austria where the State assists in organizing the popular initiative - municipality carry out all the activities associated with gathering signatures under the popular motion on submitting a draft of a bill to parliament.